1987
DOI: 10.1152/ajpregu.1987.252.2.r209
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pituitary growth hormone cells prepared from rats flown on Spacelab 3

Abstract: Anterior pituitaries from "small" (250 g) and "large" (400 g) rats flown on the 7-day Spacelab 3 mission were pooled and trypsinized into two single-cell suspensions. Compared with ground-based controls, flight cells appeared to contain more intracellular growth hormone (GH) but release less GH over a 6-day culture period. After implantation into hypophysectomized rats, both sets of flight cells released only 50% of the GH compared with the control cells. Glands from large flight rats contained 44% somatotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Consistent with the concept that there is some aspect of neuromuscular activity that might affect IGH, and especially BGH, release are observations that regulation of both hormones is disrupted in rats subjected to spaceflight or hindlimb suspension (8)(9)(10)17). For example, the release of BGH from cultured pituitary cells obtained from rats that had flown in space was attenuated (8,9).…”
mentioning
confidence: 58%
“…Consistent with the concept that there is some aspect of neuromuscular activity that might affect IGH, and especially BGH, release are observations that regulation of both hormones is disrupted in rats subjected to spaceflight or hindlimb suspension (8)(9)(10)17). For example, the release of BGH from cultured pituitary cells obtained from rats that had flown in space was attenuated (8,9).…”
mentioning
confidence: 58%
“…Perspective on BGH regulation and microgravity. Several rat studies have reported that spaceflight or hindlimb unloading decreases BGH secretion by pituitary somatotrophs in vitro and in vivo (15)(16)(17)(18)(19). In addition, human studies have shown that the normal exercise-induced plasma BGH increases that occur at 1 G are inhibited by spaceflight (23) or bed rest (22).…”
Section: Discussionmentioning
confidence: 99%
“…This response of BGH to exercise was inhibited by chronic muscle unloading during 17 days of bed rest (22) or spaceflight (23) and returned within 2-4 days of reloading. A variety of in vitro and in vivo data from rats have also shown that the release of BGH from the pituitary was inhibited by 14 days of hindlimb unloading (18) or by 7-14 days of spaceflight (15,18,19). Moreover, our laboratory recently demonstrated in rats that muscle afferent activity stimulated pituitary BGH release into the circulation and proposed that a muscle afferent-pituitary axis can modulate BGH release (11)(12)(13).…”
mentioning
confidence: 99%
“…Chronic unloading of the musculature achieved by 17 days of spaceflight (29) or bed rest (28) eliminated the normal BGH response to exercise in humans, with recovery of the response occurring after 2-4 days of reambulation. In rats, hindlimb unloading (22) or spaceflight (21)(22)(23) depressed pituitary BGH release in both in vivo and in vitro experiments. Furthermore, our laboratory demonstrated that a single bout (15 min) of intermittent electrical stimulation of large-diameter, low-threshold fibers from predominantly fast-twitch ankle extensor muscles induced BGH release in anesthetized rats (19), whereas stimulation of these afferents from a predominantly slow-twitch ankle extensor inhibited BGH secretion (18).…”
mentioning
confidence: 93%